2016
DOI: 10.1108/s1746-979120160000012006
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Complexities of Empathy Research: A Multi-Level Model of Empathy in Organizations

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 81 publications
0
25
0
2
Order By: Relevance
“…In the workplace, however, empathy has been posited as predominantly cognitive (Pohl et al , 2015) and an ability that can be shaped by the context, including leadership (Burch et al , 2016).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…In the workplace, however, empathy has been posited as predominantly cognitive (Pohl et al , 2015) and an ability that can be shaped by the context, including leadership (Burch et al , 2016).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…As emoções podem ser consideradas uma espécie de "guarda--chuva" por conta de compreenderem um grande escopo de sentimentos que os indivíduos costumam experimentar em momentos específicos de suas vidas (BARSADE; GIBSON, 2007, BRODY;HALL;STOKES, 2016). Ao estudá-las, o pesquisador pode abordá-las de forma geral ou, também, ter por foco uma única emoção como, por exemplo, amor (BRAMMING;JOHNSEN, 2011), paixão (POLLACK et al, 2020), vergonha (PLATE, 2015), medo (CAMAR-GO; LOURENÇO; FERREIRA, 2018), empatia (BURCH et al, 2016), entre outras.…”
Section: Emoções Em Estudos Organizacionaisunclassified
“…Conforme destacado no estudo de Barsade e Gibson (2007) e, também, no de Brody, Hall e Stokes (2016), não existe uma definição exata acerca de emoções e, por essa razão, elas são definidas como "termos guarda-chuva", uma vez que abrangem ampla gama de sentimentos e podem estar relacionadas a processos afetivos. Na concepção dos autores, todavia, emoções diferem de humores por serem mais dinâmicas, e podem ser estudadas de maneira geral, sem que uma específica seja destacada ou, então, podem ter por foco uma única emoção, como descrito por Bramming e Johnsen (2011), Pollack et al (2020), Plate (2015), Camargo, Lourenço e Ferreira (2018) e, também, por Burch et al (2016).…”
Section: Passo 1: Enquadramento Da Questão De Pesquisaunclassified
“…While recognizing that 'empathy' is a somewhat elusive and multifaceted concept encompassing cognitive and affective dimensions (Burch et al, 2016;Finn, 2009;Kerem, Fishman & Josselson, 2001;Smith 2006), it is suggested that definitions which emphasize cognitive aspects which centre on perspective taking are particularly relevant to collaborative knowing in management. Indeed, Somogyi et al (2013) contend that it is the perspective taking aspects of the construct which are perhaps most relevant in a management context and, as we shall see, this is substantiated from our analysis of our management practitioners' accounts, presented shortly.…”
Section: Collaborative Knowingmentioning
confidence: 99%